Current Evidences and Future Perspectives for AMPK in the Regulation of Milk Production and Mammary Gland Biology - Wu, Zhihui; Tian, Min; Heng, Jinghui; Chen, Jiaming; Chen, Fang; Guan, Wutai; Zhang, Shihai (Frontiers in Cell and Developmental Biology, 2020)
Activated protein kinase (AMP)-activated protein kinase (AMPK) senses the cellular energy status and coordinates catabolic and anabolic processes. Extensive studies have proposed that AMPK regulates energy homeostasis, cell growth, autophagy, mitochondrial biology and inflammation. The biological functions of AMPK vary in different tissues or organs. As a unique organ that produces milk, the mammary gland has recently attracted substantial research attention. This review discusses how AMPK in the mammary gland is activated by energy deprivation and heat stress via the activation of canonical and non-canonical pathways. In addition, the important downstream targets of AMPK and their functions in the mammary gland, especially during milk synthesis, are summarized in the review.